First-principles study of K, Ni and P doped superconductor AFe2As2 (A=Ba, Sr). (1st November 2022) - Li, Li; Wang, Jiajun; Cai, Juan; Liang, Yao; Cui, Yan; Tao, Hualong; Liu, Shimin; Song, Bo; Zhang, Zhihua; He, Ming
Abstract: The characteristics of structural changes, Fe magnetic moment and electron density of K, Ni and P-doped AFe2 As2 (A = Ba, Sr) were studied by first-principles calculations. After the introduction of the dopants, the Fe–As bond length and As–Fe–As angle became smaller. Although K substitution involved hole doping, Ni substitution involved electron doping, and P substitution was isovalent doping, K, Ni and P doping makes Fe and As more closely related, and the electron density near As atoms were strengthened. After doping, the distribution tendency of electron density near the As ions leads to coupling constants J 1, J 2 decreases eventually, which mean AFM order is suppressed. This redistribution of electron density is the inducement of superconductivity. Highlights: In general, The substitution reports about the superconductivity of K, Ni and P doped AFe2 As2 (A = Ba, Sr), in which the dopants were doped into different positions. We try to find the similarities and differences in the structural and electronic structural changes caused by these three different types of doping which can bring superconductivity. 1. Here we show the main characteristics of the structural changes of K, Ni and P doped AFe2 As2 (A = Ba, Sr). All Fe–As bond and As–Fe–As angle become smaller with the decreasing of Fe magnetic moment. The regularity conclusions presented here will hold for the three different doping types. 2. The exchange coupling constants J 1 and J 2 are together reduced after K, Ni and P doping, with the reducing of Fe magnetic moment, showing that the AFM order was effectively suppressed. After doping, the ground state is still collinear AFM order, and there is no sign of fierce competition between collinear AFM order and other magnetic orders. 3. Our calculation results show that there are similar characteristics in the total electron density after K, Ni and P doping. All the K, Ni and P doping leads to the As as bridge in the FeAs layer in AFe2 As2 (A = Ba, Sr) became stronger. The distribution tendency of electron density near the As ions leads to coupling constants J 1, J 2 decreases eventually, which mean the of AFM order is suppressed. This redistribution of electron density is the inducement of superconductivity.